Investigating the impacts of pit latrines on groundwater quality in Benue State, Nigeria - Aondoakaa, Stephen Chiahemba (2019)
The study investigated the impacts of pit latrines on groundwater quality in Benue State, Nigeria. A mixed methods approach was adopted for the investigation. Initially, a desk-based study using Demographic and Health Survey (DHS) data was carried out for a period of thirteen years (1999-2013) to get trends in access to improved water supply and sanitation in Nigeria and Benue State. Water testing, questionnaire administration and semi-structured interviews administration were carried out in the field. The findings showed that access to water and sanitation were low in the study areas. The DHS analysis showed that access to improved water supply in Nigeria and Benue State in form of tap water on average was below 30% for all the survey years while access to improved sanitation (flush toilets) had been below 20% on average in the survey years. In both cases, the urban areas had higher access to improved water and sanitation than the rural areas. On average, educated people had twice as much access to improved water and three times as much access to improved sanitation than uneducated people. Urban residents had an advantage over rural dwellers and wealthier people were twice as likely to have access to improved water than the poor and up to three times more likely to have access to improved sanitation. Of the wells sampled, 65% were improved and 35% were unimproved based on JMP definitions. Petrifilm count plates were used to test water for faecal coliforms. The results were considered under main categories of improved/unimproved wells, rural/urban locations and dry/wet seasons. Improved wells on the whole had 92% of contaminated samples falling into the ‘very high’ contamination range compared with unimproved wells that had 97% of the samples that showed ‘very high’ category. A breakdown into seasons and locations show that the dry season improved wells in the urban areas had 90% of samples falling into the ‘very high’ contamination group while the rural areas showed 94% in the ‘very high’ contamination range. Unimproved wells on the other hand had 95% of samples with ‘very high’ contamination in the urban areas and 100% ‘very high’ contamination in the rural areas. In the wet season, improved wells displayed 97% ‘very high’ contamination in the urban areas compared with the rural areas having 65% of samples falling in the ‘very high’ contamination group. In the case of unimproved wells, the urban areas had 95% ‘very high’ contamination while the rural areas had 69% of the samples in the ‘very high’ contamination category. Well-latrine distance, number of well users and well depth were also linked with contamination but showed a relationship of less than 30% in each of the variables investigated. On contamination awareness, 60% of urban respondents and 73% of rural respondents reported being aware of poor water, sanitation and others causing diseases from contamination. Water treatment (improved) was carried out by 78% and (unimproved) 22% of urban dwellers compared with (improved) 87% and (unimproved) 13% of those in the rural areas. Most of the treatments were straining the water through a cloth which is not effective according to JMP. The poor level of access to water and sanitation reported in the DHS surveys was confirmed in the field. Consequently, 40% of urban respondents and 66% of rural respondents reported being affected or having relatives affected with water-related diseases such as typhoid or diarrhoea. The government was not able to provide potable water for the people and 38% urban and 64% rural people opined that the provision of tap water by the government would help to solve the water problems. General environmental sanitation was also poor with some contamination risks observed and photographed. In the semi-structured interviews many respondents, in the dry season, especially in the rural areas travelled or waited at water collection points for an average of three hours to get drinking water from boreholes and unprotected springs. The scarcity of water in the dry season affected sanitation and hygiene practices. Many people were not aware of groundwater contamination, confirming findings from questionnaire surveys. The government agencies acknowledged contamination issues but identified funding, labour shortages, equipment and other logistics issues to have limited their performance. It was recommended that issues militating against government agencies’ operations should be addressed so that the people can be provided with potable water in the form of tap water to ease the problem of poor water supply and water borne diseases. Low cost sanitation and more hygiene practises were also recommended.